Soil erosion and sediment yield analysis in semi-arid Tanzania (case study of Kongwa District) - Mbaga, D.A. (Ardhi University, 2022)
Soil erosion is a most devastating geological hazard and it is a severe problem in central Tanzania especially in the semi-arid regions, and the resultant sediment yield creates threats to sustainable agriculture and ecosystems. But the execution of different mitigation initiatives and policies used to adopt conservation practises in agricultural lands are unsuccessful or in effective due to the lack of spatial information on soil erosion areas. This study attempts to analyze soil erosion prone areas and sediment yield in the Kongwa district using GIS and remote sensing technique. The Revised Universal Soil Loss Equation (RUSLE) was used to estimate potential soil losses and sediment yield by utilizing rainfall, soil, Normalized Difference Vegetation Index(NDVI) and Digital Elevation Model (DEM) datasets. The results obtained demonstrate high soil erosion prone areas in the southern part of the Kongwa district, with the average annual soil loss equal to 66.24ton/ha/year and sediment yield of about 13.58 ton/ha per year. Generally, soil erosion prone areas have been idenified and sediment yield have been generated to support decision making processes regarding development of soil erosion control and adaptive measures for sustainable environment conservation measures. Based on the results obtained it is recommended that the sensitivity analysis of RUSLE model parameters should be carried out.